Impacts of unplanned settlement in the southern part of the jaffna town - Raveendran, S.; Tharani, J. (university of Jaffna, 2014)
Unplanned settlement which is an outcome of rapid urbanization where planning [1] mechanism inefficient to control, creates number of issues and problem at local and global scales . Jaffna Town experiences socio, economic, environmental issues of unplanned settlement which is [10] triggered by fast phase of urbanization in the region . The aim of this research is formulate strategies to manage the impacts caused by the unplanned settlement in Southern part of Jaffna Town. The objectives of the research were to assess the existing pattern of unplanned settlements, to identify the causes of unplanned settlement, to assess the impacts of unplanned settlement development finally to propose suitable methods to curb the unplanned development and to promote sustainable settlement development. Spatial data were collected regarding causes and effects of unplanned settlements in Jaffna Town through questionnaire survey on household information and facilities. Field measurements were obtained regarding planning and building regulation. Social and physical infrastructure facilities in the study areas were assessed based on the minimum standards required for a community. Authorities responsible for urban planning and development were interviewed. Data and information were analyzed based on planning principles using descriptive analysis techniques. According to the research 85% of the dwellings constructed contrary to the rules and regulation and 95% of the dwellings are unauthorized. The causes of unplanned development identified were lack of space, higher land value, inefficient regulations, lack of planning measures, poverty etc. This research insists the following recommendations to be implemented to create livable communities; implementation of regulations need very dynamic approach where peoples' needs must be met while maintaining the regulation, promoting vertical living, and provision of suitable social and infrastructure facilities.
Keywords: Unplanned settlement; Urbanization; Urban planning; Planning regulations